1967
DOI: 10.1042/bj1020983
|View full text |Cite
|
Sign up to set email alerts
|

The ion-binding characteristics of reconstituted collagen

Abstract: The ion-binding capacity of highly purified reconstituted calf-skin collagen, and the effects of these ions on the precipitation and solubility of the collagen, were studied with a variety of salt solutions at ionic strength 0.16 and pH7.4. Only a small percentage of the total theoretically available anionic and cationic groups was available for ion-binding. In view of this, it appears that most of the ionizable groups of collagen are involved in intramolecular or intermolecular linkages, or both. Nevertheless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

1968
1968
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 23 publications
1
15
1
Order By: Relevance
“…35 It was demonstrated that solution pH can affect the electrochemical property of collagen, such as the dissociation of the acidic and basic groups of collagen molecules 37,38 and ion-binding characteristics of collagen fibrils. 39 The isoelectric point of tropocollagen of calf skin 37 is reported to be pH 8.3 and that of pig skin gelatin 38 is approximately pH 9.4. Therefore, the more basic the solution is, the more anionic residues are available in the collagen molecules to react with Ca 2+ ions.…”
Section: Discussionmentioning
confidence: 99%
“…35 It was demonstrated that solution pH can affect the electrochemical property of collagen, such as the dissociation of the acidic and basic groups of collagen molecules 37,38 and ion-binding characteristics of collagen fibrils. 39 The isoelectric point of tropocollagen of calf skin 37 is reported to be pH 8.3 and that of pig skin gelatin 38 is approximately pH 9.4. Therefore, the more basic the solution is, the more anionic residues are available in the collagen molecules to react with Ca 2+ ions.…”
Section: Discussionmentioning
confidence: 99%
“…A second potential explanation incorporating electrostatic effects must be included: the results could also be explained by selective ion adsorption along the molecular backbone, resulting in an increased charge density that overwhelms the screening effects. The effect of selective ion adsorption was observed by Docking and Heymann and further investigated by Weinstock et al In the Weinstock study, type I collagen was suspended in solutions varying in species and concentrations of ions. The ions were then dialyzed out of solution.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, PAH-ACP should not have been attracted to the other band sites (e.g. b, c and d bands) because charges of the ionic residues in the fibrillar polyampholyte are internally compensated along those locations 24,25 .…”
Section: Pah-acp Induced Intrafibrillar Mineralisationmentioning
confidence: 99%